2017
DOI: 10.1002/2016jb013565
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of southern Madagascar from receiver functions and ambient noise correlation: Implications for crustal evolution

Abstract: The Precambrian rocks of Madagascar were formed and/or modified during continental collision known as the Pan‐African orogeny. Aborted Permo‐Triassic Karoo rifting and the subsequent separation from Africa and India resulted in the formation of sedimentary basins in the west and volcanic activity predominantly along the margins. Many geological studies have documented the imprint of these processes, but little was known about the deeper structure. We therefore deployed seismic stations along an SE‐NW trending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 81 publications
4
45
0
Order By: Relevance
“…In contrast, there are no significant differences in Poisson's ratio between the Archean crust (0.25 ± 0.02) and Proterozoic crust (0.26 ± 0.04) or in average shear wave velocities (3.7 km s -1 for both), though the average thickness of the mafic lower crust is slightly greater for Archean terranes (7 km) than it is for Proterozoic terranes (4 km). Our results are in broad agreement with Rindraharisaona et al (2017). They concluded that the Archean crust is also slightly thicker (38-43 km) compared to the Proterozoic crust (33-38 km).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, there are no significant differences in Poisson's ratio between the Archean crust (0.25 ± 0.02) and Proterozoic crust (0.26 ± 0.04) or in average shear wave velocities (3.7 km s -1 for both), though the average thickness of the mafic lower crust is slightly greater for Archean terranes (7 km) than it is for Proterozoic terranes (4 km). Our results are in broad agreement with Rindraharisaona et al (2017). They concluded that the Archean crust is also slightly thicker (38-43 km) compared to the Proterozoic crust (33-38 km).…”
Section: Discussionsupporting
confidence: 82%
“…S4, in this study), a clear phase, presumably the Ps wave converted from the Moho discontinuity, is observed at ∼4 s. This indicates thinner crust (∼36 km) as reported in this study and earlier ones using receiver functions (e.g. Rindraharisaona et al 2013Rindraharisaona et al , 2017, which used more than one station along the eastern coast and considered broader back azimuth ranges. In support of this interpretation, crustal thickness estimates from gravimetry imply that the crust thins towards the eastern coast (Fourno & Roussel 1994;Rakotondraompiana et al 1999).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We used the results of Rindraharisaona et al () to construct starting velocity models for the Rayleigh wave inversion. For the subsequent Love wave inversion, the final velocity structure derived from the Rayleigh wave inversion was used as the starting model (R L ordered inversion).…”
Section: Methodsmentioning
confidence: 99%
“…In order to test the dependence of the inversion on the starting model, we performed R L and L R ordered inversions using six different velocity models: two gradient models and four realistic models representing the subregions of southern Madagascar, that is, the Morondava basin, Proterozoic domains, Archean domains, and Cretaceous volcanics (along the east coast). The realistic models were generated from the results of Rindraharisaona et al () by taking the median velocity for each layer from the models for all stations in each subregion. Although each of the grid nodes is located in just one of the four subregions, we always tested all six starting models to assess the uniqueness of the inversion.…”
Section: Methodsmentioning
confidence: 99%